(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
In the present study the partial pressure of oxygen (PaO2), carbon dioxide (PaCO2) and bicarbonate ion (HCO3-) in arterial blood were estimated in 32 women in Dhaka city. For this purpose a total of 32 women subjects with age ranged from 25 years to 35 years without any recent history of respiratory diseases were selected. Of those, 8 healthy non-pregnant women were included as control and 24 normal pregnant women as experimental group. The PaO2, PaCO2 and HCO3- were estimated during the first, second and third trimester by using ’easy blood gas auto analyzer’. The PaO2 was significantly higher during entire pregnancy period. However, the PaCO2 and HCO3- were significantly lower in first, second and third trimester of pregnant women than that of non-pregnant women. There were no statistically significant difference of PaO2, PaCO2 and HCO3- ion among first trimester, second trimester and third trimester. The progressively increased PaO2, decreased PaCO2 and HCO3- ion throughout the pregnancy is possibly due to the effect of progesterone causing hyperventilation. DOI: 10.3329/bjpp.v23i1.5724 Bangladesh J Physiol Pharmacol 2007; 23(1&2) : 10-12